Implementing the IMPALA continuous monitoring system for paediatric critical care in Malawi: A mixed methods study of barriers and facilitators - Daniel Mwale; Christopher Pell; Jobiba Chinkhumba; Happiness Mandala; Jessica Chikwana; Josephine Langton; Alice Likumbo; Michael Boele van Hensbroek; Job Calis; Wendy Janssens; Lucinda Manda-Taylor (PLoS ONE, 2025)
Introduction Continuous monitoring of critically ill children is essential for the timely identification of deteriorating vital signs. However, monitoring is often intermittent in low-resource settings, affecting the quality of care. This study assessed the implementation barriers and facilitators of a locally adapted, robust, low-cost continuous monitoring system (IMPALA) in Malawi. Methods A mixed-method implementation study of the IMPALA system in the paediatric High-dependency unit of a tertiary hospital from November 2022 to October 2023. Data were collected through over 300 hours of observations, in-depth interviews with 14 healthcare providers and nine caregivers of admitted children, and questionnaire-based surveys from 24 healthcare providers and 72 caregivers. Qualitative data were analysed thematically using inductive and deductive approaches. Descriptive statistics (frequencies, percentages, means, and standard deviations) were calculated for categorical and continuous variables. Results Healthcare providers and caregivers indicated that the IMPALA monitors improved care by providing the ability to measure reliably multiple vital signs, with long-lasting (4 hours) backup power and alarm provisions. Healthcare providers reported spending less time on child monitoring after the introduction of IMPALA (1.8 hours per day pre-IMPALA (95% CI: 1.19–2.48) compared to 3.3 hours post-IMPALA (95% CI: 2.36–4.23; p < 0.00). Still, they recognised alarm fatigue, limitations in knowledge of the technology, and staff shortages as barriers to the use of IMPALA. Some caregivers expressed concerns about the reliability of the monitoring system. Conclusion The continuous monitoring device was well-received overall by healthcare providers and caregivers. It was perceived to save time and improve the quality of care. Opportunities to further enhance engagement with the device include strengthening caregivers’ knowledge and involvement to address their mistrust or misconceptions about the device, minimising false alarms, and providing ongoing training to healthcare providers so that new, existing, and rotating staff know how to engage with the device.